Radiation shielding performance of CeO2-reinforced ternary nanocomposites based on biodegradable polymers and waste-derived polystyrene - Pekdemir, Mustafa Ersin; Yilmaz, Demet; Pekdemir, Sibel Selcuk; Gulhan, Aleyna; Kuzu, Serpil Yalcin; Altun, Sedanur; Tasgin, Yahya (Pergamon-Elsevier Science Ltd, 2026)
The development of sustainable polymer-based materials for radiation shielding has attracted increasing interest, particularly for lightweight and flexible applications. In this study, ternary nanocomposites based on poly (hydroxyalkanoate) (PHA), poly (epsilon-caprolactone) (PCL), and polystyrene (PS) were prepared and reinforced with cerium oxide (CeO2) nanoparticles (5-15 wt%) to enhance radiation shielding performance. Structural characterization confirmed the preservation of polymer chemical structures and the successful incorporation of crystalline CeO2, while SEM observations revealed a relatively homogeneous nanoparticle dispersion within the ternary matrix, particularly at intermediate filler loadings. Thermal analysis demonstrated enhanced thermal stability with increasing CeO2 content, as evidenced by an increase in residual mass from 0.42% for the neat blend to 11.21% for the nanocomposite containing 15 wt% CeO2, along with a shift of degradation onset temperatures toward higher values. Photon shielding performance was experimentally evaluated in the energy range of 13.37-59.54 keV. The incorporation of 15 wt% CeO2 increased the mass attenuation coefficient (MAC) from 1.277 to 12.366 cm2 g-1 at 13.37 keV, corresponding to an approximately ninefold enhancement, while significantly reducing the half-value layer (HVL) and mean free path (MFP). Neutron shielding analysis showed a slight decrease in thermal neutron attenuation due to hydrogen dilution within the polymer matrix, whereas fast neutron attenuation and neutron removal cross sections exhibited only minor variations; the fast neutron removal cross section increased modestly from 0.1014 to 0.1047 cm-1 with 15 wt% CeO2 addition. Overall, the results highlight clear structure-property-performance relationships in CeO2-reinforced PHA/PCL/PS nano composites, demonstrating their potential as lightweight radiation shielding materials for low energy protection with improved thermal stability and shielding efficiency.
Keywords: Polymer Nanocomposites; Ternary Polymer Blends; Cerium Oxide Nanoparticles; Radiation Shielding; Thermal Stability